Determination of Roughage Adequacy by Means of Animal Husbandry Status and Feed Sources in the KOP Region - Orhan Ermetin; Mevlüt Mülayim (Turkish Journal of Agriculture: Food Science and Technology, 2020)
KOP region covers Aksaray, Karaman, Konya, Niğde Nevşehir, Yozgat, Kırıkkale and Kırşehir provinces. KOP region has an area of 95,580 km² about 12,3%, with 4.515.046 population about 5,4% and 12,3% of agricultural lands of Turkey. KOP Region has 13.1 % grassland and 9,4% of the area of forage crops cultivation and in terms of production forage crops 15,8% of Turkey. KOP region has also 2.150.920 head of cattle (11,8% of the Turkey), and whit 5.431.031 head of small ruminant (%10,9 of the Turkey). 3.032.086 tons of milk is produced in the KOP region (13,2% of the Turkey). It is produced in the KOP region that 11,9% of Turkey's total red meat production. Livestock and forage crops production has an important place in 8 provinces of the KOP region. In this study, the current situation of livestock, pasture and forage crops cultivation in KOP provinces were evaluated and its effects on regional and country development were examined. Since there are 1.608.530 tons of forage deficit in the KOP region, the production of forage should be increased. In order to increase animal production in the region by the KOP Administration, efforts towards expanding modern techniques and improving livestock infrastructure should continue and animal husbandry activities should continue to be supported with new projects.